2011
DOI: 10.1007/s11011-011-9259-5
|View full text |Cite
|
Sign up to set email alerts
|

The streptozotocin-induced rat model of diabetes mellitus evidences significant reduction of myosin-Va expression in the brain

Abstract: Diabetes mellitus is a disease characterized by increased glucose levels in the blood. Hyperglycemia causes damage to the brain tissue, and induces significant changes in synaptic transmission. In this investigation, we have found a significant alteration in the expression of the molecular motor involved in the synaptic vesicles transport, myosin-Va, and its distribution in rat brains of streptozotocin-induced diabetes model. Brains were removed after 20 days, homogenized and analysed by Western blotting, qRT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
1
11
0
1
Order By: Relevance
“…Myosin-IIB modulates neurotransmitter release from synapses [83] while myosin-Va mediates synaptic vesicle trafficking [84]. We recently demonstrated that acute diabetes (20 days) alters protein and mRNA expression of myosin-IIB and myosin-Va in the rat brains [21, 23]. In the present study, we revealed an increased protein and mRNA expression of myosin-IIB and a decreased one of myosin-Va in chronic diabetic rat brains (90 days).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Myosin-IIB modulates neurotransmitter release from synapses [83] while myosin-Va mediates synaptic vesicle trafficking [84]. We recently demonstrated that acute diabetes (20 days) alters protein and mRNA expression of myosin-IIB and myosin-Va in the rat brains [21, 23]. In the present study, we revealed an increased protein and mRNA expression of myosin-IIB and a decreased one of myosin-Va in chronic diabetic rat brains (90 days).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we revealed an increased protein and mRNA expression of myosin-IIB and a decreased one of myosin-Va in chronic diabetic rat brains (90 days). It is possible that these translational and transcriptional changes are due to low insulin level and high glucose level in circulation providing a possible dysfunction in vesicle/organelle movement [21, 23]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…injection of 10% chloral hydrate (500 mg/kg) at day 1, 3, 7, 14 and 30 following-SE induction. Following decapitation, the brain was removed as previously described (17) for RNA isolation. Total RNA was extracted with TRIzol reagent (Gibco; Thermo Fisher Scientific, Inc., Waltham, MA, USA) and both the concentration and the purity of RNA were then determined at 260/280 nm using a NanoDrop spectrophotometer.…”
Section: Animalsmentioning
confidence: 99%
“…Similarly, nNOS uncoupling has been shown to be responsible for dysfunctional nitrergic vasorelaxation of penile arteries from insulin-resistant obese Zucker rats [10]. Recently, expression of myosin Va has been reported to be reduced in neuronal tissues from the brain of animal models of diabetes mellitus [33]. Thus it is interesting to speculate that myosin Va defects may contribute to the pathogenesis of diabetic gastroparesis and erectile dysfunction.…”
Section: Discussionmentioning
confidence: 99%